GRADUATED PHARMACISTS PROMOTING ORAL HEALTH IN FEDERATION OF BOSNIA AND HERZEGOVINA (Zdravstveni glasnik, 2024)
Background: Community pharmacists are healthcare professionals that play a crucial role in delivering quality healthcare to people, including oral health-related problems and dental hygiene products, as part of health promotion.In order to better understand these issues in FB&H, this exploratory study aimed at assessing the knowledge, attitude and practice of Pharmacy interns in Federation of B&H in regard to oral health and their educational needs, with the ultimate goal of enhancing their future role in promoting oral health and oral hygiene practices as pharmacists.Methods: This cross-sectional study was carried out among pharmacy interns in 2019 by using self-administered, semi-structured questionnaire. The results were statistically analysed using descriptive statistics.Results: The most frequently reported oral condition/products on which pharmacists provided advice during their practice were: (other) gum related problems like pain, redness, tenderness, inflammation etc.), Toothache and Denture related problems. Mouthwash, Toothbrush and Toothpaste were reported respectively. Regarding the knowledge of participants about prevention oriented oral health behaviours, 80.8% of participant strongly agree and agree to recommended oral health behaviors. Participants showed positive attitudes toward their role in oral health care and willingness to improve their knowledge about this issue. Conclusion: This study shows that pharmacy interns in FB&H have good knowledge about preventive oral health behaviours, average knowledge related to oral health care and have positive attitude to their important role in maintenance of oral health despite all barriers and difficulties. The pharmacist interns expressed their need for education/training to enhance their practice.